ELEMENTY FILOZOFII CYNICKIEJ W EDUKACJI SZKOLNEJ W OKRESIE PÓŹNEGO CESARSTWA RZYMSKIEGO - Iwo Szoka, Andrzej (In Gremium. Studies in History, Culture and Politics, 2017)
ELEMENTS Of CYNIC PHILOSOPHY IN PRIMARY EDUCATION DURING THE ERA Of THe LATE ROMAN EMPIRE Ancient Cynicism was a philosophy practiced up to the 4th century A.D. Among the key sources that describe the activities of Cynics during this period are two speeches by the Roman emperor, Julian (361-363). Within these two speeches he criticized the contemporary supporters of Cynicism. Julian had extensive knowledge about the rules of Cynicism and about the lives of its founders: Antisthenes, Diogenes of Sinope, and Crates of Thebes. He possibly acquired this knowledge during his philosophical studies. It is possible, however, that the future emperor came into contact with cynicism much earlier, during a period of his primary education in Nicomedia between 338 and 342. Elements of Cynicism, especially the figure of the famous Diogenes the Dog, were presented at the Greek-speaking school in reading and writing courses. It was so because of the widespread popularity of Greek chreia in which the Sinopean philosopher was a main character. The chreiae with Diogenes as the main figure were also used in higher levels of education, including the schools of rhetoric. Such popularity of Cynic chreia in primary education is confirmed by the texts used in the classroom, preserved among the papyri, and in the handbooks of rhetorical art. We can’t exclude that in some cases young students chose a Cynic lifestyle under the influence of the philosophy of Cynicism and the legend of Diogenes, which he learned about during his primary education.